2020
DOI: 10.3389/feduc.2020.571150
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning of Brazilian Students in a Teacher Education Program in Piaui: The Impact of a Self-Regulation Intervention

Abstract: Research on teacher education has shown that self-regulated learning (SRL) is relevant for improving learning skills of future teachers. Evidence also suggests that teacher education programs would benefit from fostering SRL in their students and teaching them to use SRL as a teaching practice. This dual focus could help students become more successful students and teachers, better prepared to foster SRL in their future classrooms. The objective of the present research was to investigate learning and study str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
1
4
0
1
Order By: Relevance
“…Results show that students generally report using learning and study strategies, with some strategies being reported more than others. These findings converge with research on strategic and self-regulated learning (Arcoverde et al, 2020;Iqbal et al, 2010;Pavesi & Alliprandini, 2016). The attitude scale showed the highest score.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Results show that students generally report using learning and study strategies, with some strategies being reported more than others. These findings converge with research on strategic and self-regulated learning (Arcoverde et al, 2020;Iqbal et al, 2010;Pavesi & Alliprandini, 2016). The attitude scale showed the highest score.…”
Section: Discussionsupporting
confidence: 86%
“…Though there are several models of self-regulated learning (Panadero, 2017), we chose to focus on both the Model of Strategic Learning (Weinstein, 1994) and the self-regulated learning model (Zimmerman, 2000(Zimmerman, , 2002 as theoretical frameworks because, as mentioned in Arcoverde et al (2020), the models of Weinstein (1994) and Zimmerman (2000Zimmerman ( , 2002 consider learning a complex process, which involves the regulation of cognitive, metacognitive, motivational, affective and behavioral factors.…”
Section: Conceptual Models Of Strategic and Self-regulated Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Selfregulated learning strategies are generally associated with the perceived benefit of virtual patient learning activities, but external teacher and peer regulation are productive for increasing learners' perceived benefit (Edelbring & Wahlström, 2016). A self-regulated learning intervention showed significant gains in learning skills and self-efficacy for learning among undergraduate students enrolled in a teacher education program (Arcoverde et al, 2020).…”
Section: Internal and External Motivationmentioning
confidence: 99%
“…(Wolters y Hussain, 2015). Esta complejidad conceptual ha favorecido el desarrollo de un amplio campo de investigación, destacando aquellos estudios que promocionan los procesos de auto-regulación en estudiantes a través de la creación y aplicación de programas y miden sus efectos (Arcoverde, Boruchovitch, Acee, y Góes, 2020;Hernández y Camargo, 2017;Rosário et al, 2014).…”
Section: Auto-regulación De Aprendizajeunclassified